Acid-Base Balance and Blood-Gas Analysis in Bronchopneumonia in Infancy and Childhood - Mardjanis Said; I. Boediman; Nastiti N. Rahajoe; Noenoeng Rahajoe (Indonesian Pediatric Society, 1980)
Arterial Blood-Gas and pH changes were studied in sixty-three infants and children aged 6 years or less, with severe and uncomplicated bronchopneumonia, which was proven clinically and radiologically. Fifty-five (87.3%) patients showed a ventilatory insufficiency (PaC02 below 35 mmHg). Only 3 (4.8%) cases were found with carbon retention as a sign of ventilatory failure (PaC02 above 45 mmHg). Twenty-eight (44.4%) cases had metabolic component. The suggested causes of metabolic acidosis in these cases were the inflammatory process in the lungs itself which caused hypoxia, and a low intake during their sickness prior to admission to the hospital.